Dinâmica econômica e empresariamento urbano em cidades médias sob o impacto da reestruturação produtiva - Terci, Eliana T.; Goulart, Jefferson O.; Otero, Estevam V. (Nova Economia, 2017)
Abstract: The article comparatively analyzes contemporary urban development processes of medium-sized cities taking into account the restructuring process in the context of economic liberalization occurred from the 1990s to 2011. The empirical basis consisted of three medium-sized cities in the state of São Paulo: Piracicaba, Bauru and Rio Claro. The data on economic development and public spending showed the predominance of business interests in the management of these cities with the purpose of making them attractive for private investment occasioning urban entrepreneurship. On the one hand, this scenario is connected to the emptying of the state and its urban and regional development policies and on the other hand, there is the new leading role of municipalities in the effort to readjust their productive structures to attract private enterprises.

Resumo: O artigo analisa comparativamente processos contemporâneos de desenvolvimento urbano de cidades médias, tendo em conta o processo de reestruturação produtiva no contexto da liberalização econômica a partir da década de 1990 até 2011. A base empírica consistiu de três cidades médias do interior paulista: Piracicaba, Bauru e Rio Claro. Os dados sobre o desenvolvimento econômico e o gasto público evidenciam o predomínio de interesses empresariais na gestão dessas cidades com a finalidade de torná-las atrativas para as inversões privadas, ensejando o empresariamento das cidades. A ação do poder público local se revelou determinante para a dinamização da economia urbana e regional. Esse cenário está ligado, de um lado, ao esvaziamento do Estado e de suas políticas de desenvolvimento urbano e regional e, de outro, ao novo papel destacado dos municípios no esforço de readequação de suas estruturas produtivas visando a atrair os empreendimentos privados.
Economic dynamics and urban entrepreneurship in medium size cities under the impact of productive restructuring
Keywords: economic liberalization; restructuring of production; urban entrepreneurship; medium-sized cities; liberalização econômica; reestruturação produtiva; empresariamento urbano; cidades médias